(3QSGdI aj TQM GdMOjK GdGQHYjfs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMOjK GdChd hdGJYSQhG hGHTQhG hdGJaQhG bGd Gddg JYGdi (B: ( (3hPcQ aEf GdPcQi JfaY GdeDefjf (B) s
(3BNQgG (B:s
(3hbGd CHh GdYHGS Hf TQjM ai QNUI dYHI GdTWQfL Mjf SFd Yfg EPG SdeJ CjOjgeG ef GdWajGf hdSGfgeG ef GdgPjGf s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1036s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs